Fifteen-year single-center experience with pediatric pyeloplasty: surgical outcomes and reoperation rates from 2010 to 2025 - Elkassaby, Abdelhameed A.; Mostafa , Mohamed S. (International Surgery Journal, 2025)
Background: Ureteropelvic junction obstruction (UPJO) is a leading cause of pediatric hydronephrosis, often requiring surgical correction to prevent progressive renal damage. Despite innovations in minimally invasive techniques, long-term data on surgical durability and reoperation rates remain limited. Methods: The study was conducted in the Royal Aberdeen Children’s Hospital. We conducted a retrospective review of 66 consecutive pediatric pyeloplasties performed at a tertiary center from January 2010 to December 2025. We collected data on patient demographics, surgical approach (open vs. laparoscopic), operative metrics, complications, and reoperation incidence. Outcomes were analyzed using χ² tests for categorical variables and ANOVA for continuous variables, with logistic regression for predictors of reoperation. Results: Of the 66 patients (mean age 5.2±3.6 years; 66.7% male), the proportion receiving laparoscopic repair rose from 0% to 88% over the study period. Overall reoperation rate was 6.1% (n=4), with the highest risk in infants <6 months (12.0%) and those with severe calyceal dilatation (9.5%). Mean operative time decreased from 145±30 min in 2010–2014 to 92±18 min in 2020–2025. No major (Clavien–Dindo ≥III) complications occurred. Conclusions: Pediatric pyeloplasty at our institution demonstrates excellent long-term success. The shift to laparoscopic technique has improved perioperative efficiency without compromising outcomes. Targeted strategies are warranted for high-risk subgroups, and ongoing surveillance of functional and patient-centered metrics will enrich decision-making.